PENGARUH PEMBERIAN PUPUK SUPER PALMAS DAN PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI HIJAU (Brassica juncea L.) - Dika Al Azhar; Elfin Efendi; Lokot Ridwan Batubara (Universitas Asahan, 2020)
The research was conducted at the Asahan University Faculty of Agriculture research field, Jalan Latsitarda, Kisaran Naga Village, Kisaran Timur District, Asahan Regency, North Sumatra Province in March to May 2019 using a Factorial Randomized Group Design consisting of two factors and three replications. The first factor is the application of the superficial doses of fertilizer (S): S0 = 0 ml / liter of Water, S1 = 10 ml / liter of Water, S2 = 20 ml / liter of Water, and S3 = 30 ml / liter of water. The second factor is the application of pearl NPK fertilizer dosage (N): N = 0 g / plot, N1 = 25 g / plot, and N2 = 50 g / plot. Observation variables consist of Plant Height, Number of Leaves, Production per plant sample, and production per plot. The results showed that the administration of super palmas fertilizer showed no significant effect on all parameters of plant observations. The administration of pearl NPK fertilizer showed no significant effect on all parameters of plant observations. And the interaction of super palmas fertilizer and pearl NPK fertilizer showed no significant effect on all parameters of plant observations.